On the ALMA observability of nascent massive multiple systems formed by gravitational instability. Issue 4 (10th June 2019) - Meyer, D M-A; Kreplin, A; Kraus, S; Vorobyov, E I; Haemmerle, L; Eislöffel, J
ABSTRACT: Massive young stellar objects (MYSOs) form during the collapse of high-mass pre-stellar cores, where infalling molecular material is accreted through a centrifugally balanced accretion disc that is subject to efficient gravitational instabilities. In the resulting fragmented accretion disc of the MYSO, gaseous clumps and low-mass stellar companions can form, which will influence the future evolution of massive protostars in the Hertzsprung–Russell diagram. We perform dust continuum radiative transfer calculations and compute synthetic images of disc structures modelled by the gravito-radiation-hydrodynamics simulation of a forming MYSO, in order to investigate the Atacama Large Millimeter/submillimeter Array (alma ) observability of circumstellar gaseous clumps and forming multiple systems. Both spiral arms and gaseous clumps located at ≃ a few $100\, \rm au$ from the protostar can be resolved by interferometric alma Cycle 7 C43-8 and C43-10 observations at band 6 ($1.2\, \rm mm$ ), using a maximal 0.015 aracsec beam angular resolution and at least $10\!-\!30\, \rm min$ exposure time for sources at distances of $1\!-\!2\, \rm kpc$ . Our study shows that substructures are observable regardless of their viewing geometry or can be inferred in the case of an edge-viewed disc. The observation probability of the clumps increases with the gradually increasing efficiency of gravitational instability at work as the disc evolves. As a consequence, large discs around MYSOs close to the zero-age-main-sequence line exhibit more substructures than at the end of the gravitational collapse. Our results motivate further observational campaigns devoted to the close surroundings of the massive protostars S255IR-NIRS3 and NGC 6334I-MM1, whose recent outbursts are a probable signature of disc fragmentation and accretion variability.